The role of student counselling in school leadership : case study in Finnish and Russian schools - Mironova, Sima (2016)
The aim of my master's thesis research is to understand student counselling phenomenon and its role in Russian and Finnish school leadership. This research study shows differences of organising student counselling in schools itself and its role in a school leadership. Lifelong learning as a part of student counselling provides deep understanding of a counselling process and its importance of student's development. Qualitative research method is chosen as a research method and semistructured interview as a data collection method. There were a need of conducting six interviews in one Finnish school and five interviews in one Russian school. Thematic coding and network analysis were used to answer the four research questions. The results of case studies show that the student counselling is a part of school leadership in Finnish school, there is no place for it in Russian school leadership. Lifelong learning in Finnish perspective has accent on student's encouragement to be independent thinkers and continuous learners. Russian school takes a passive role in student’s readiness for lifelong learning. The further recommendation for study is to investigate lifelong-learning concept and to conduct research which will show the influence of lifelong-learning policies in educational systems on student's performance at school.